2021
DOI: 10.1365/s40702-021-00815-y
|View full text |Cite
|
Sign up to set email alerts
|

AR/VR.nrw – Augmented und Virtual Reality in der Hochschullehre

Abstract: ZusammenfassungImmer mehr Hochschulen suchen nach Lösungen Augmented und Virtual Reality (AR/VR) stärker in Lehre und Forschung einzubinden. Es wurde bereits gezeigt, dass für manche Sachverhalte immersive Technologien verglichen mit traditionellen Lernmethoden besser geeignet sind; speziell um komplexe Sachverhalte zu erleben und zu lernen. Abseits solcher Projekte finden sich jedoch kaum Fälle einer breiten Anwendung in der gängigen Hochschullehre. Mit diesem Beitrag wird eine Möglichkeit vorgestellt, Augmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…Der VR-Technologie wird nachgesagt, sie besitze das Potenzial, die akademische Lehre und medizinische Weiterbildung zu verbessern (Ghanem und Osterhoff 2020). Studierende werden in ihrem Lerninteresse motiviert und können sich durch die Reduktion der äusseren Einflüsse auf den Lerngegenstand besser fokussieren (Müser und Fehling 2022).…”
Section: Stand Der Forschungunclassified
“…Der VR-Technologie wird nachgesagt, sie besitze das Potenzial, die akademische Lehre und medizinische Weiterbildung zu verbessern (Ghanem und Osterhoff 2020). Studierende werden in ihrem Lerninteresse motiviert und können sich durch die Reduktion der äusseren Einflüsse auf den Lerngegenstand besser fokussieren (Müser und Fehling 2022).…”
Section: Stand Der Forschungunclassified
“…The literature review that was conducted as the basis for this paper showed that various studies have been conducted to evaluate the implications, limitations and applications of the metaverse for education and that the first immersive or metaverse campuses and applications are available [27][28][29][30]. The majority of the studies show that education could be improved by using immersive technologies, such as VR, AR or the metaverse [31][32][33][34].…”
Section: Education In Metaversementioning
confidence: 99%
“…The extraneous cognitive loads describes the externalities of the learning material, the learning environment and the general conditions [72]. That means, that the materialities and functions in the metaverse need to be reduced to a minimum to avoid cognitive expenditure on resources for superfluous processes [30]. In Figure 7 it can be seen, that the metaverse has advantages in various ways.…”
Section: The Metaverse Offers a More Attractive Learning Environment ...mentioning
confidence: 99%
See 1 more Smart Citation
“…VR technology has received great attention from various fields at the beginning, but due to its expensive development cost, it is generally only developed for special purposes. With the rapid development of computer science and artificial intelligence technology [ 3 ], VR technology can be said to be changing with each passing day, not only the great improvement in “3I” characteristics, but also the accompanying introduction of personal consumer VR products [ 4 ], which makes the popularization and application of VR technology possible [ 5 ]. At present, VR technology is being widely used in public safety, industrial design, medicine, planning, transportation, culture and education, and other industries and departments [ 6 ].…”
Section: Introductionmentioning
confidence: 99%